Distal Medial Collateral Ligament Avulsion Repair - Griffin R. Rechter, M.D.; Lindsay Barrera, M.D.; Adam V. Daniel, M.D.; Mario Hevesi, M.D., Ph.D.; Aaron J. Krych, M.D.; Adam Tagliero, M.D.; Bruce A. Levy, M.D. (Arthroscopy Techniques, 2025)
The ability of the knee to resist valgus stress is largely a result of the integrity of the superficial medial collateral ligament (MCL) and neighboring supporting structures (i.e., deep MCL, semimembranosus, and posterior oblique ligament). The MCL is known to have a robust healing capacity; consequently, the decision to proceed with operative versus nonoperative management of even grade III MCL tears is controversial. When it comes to operative management of these injuries, the decision to proceed with repair or reconstruction is nuanced because the chronicity and location of the MCL tear (i.e., proximal, midsubstance, or distal) largely determine which technique is appropriate. In distal MCL avulsions, including the so-called Stener lesion, with good tissue quality, direct MCL repair has shown excellent mid-term outcomes. Consequently, there is a growing need to understand different techniques to address MCL incompetence. In this article, we present a method for primary MCL repair using a washer post–suture post construct.